Resilience-Building Technologies: State of Knowledge -- ReSIST NoE Deliverable D12 - Strigini, L. (2007)
This document is the first product of work package WP2, "Resilience-building and -scaling technologies", in the programme of jointly executed research (JER) of the ReSIST Network of Excellence